Treatment Duration and Its Impact on the Number of Polymorphonuclear, Mononuclear and Neutrophil Lymphocyte Ratio as Indicators of Recovery Rate in Tuberculosis Patients - Aini Aini; Fihiruddin Fihiruddin; Maruni Wiwin Diarti; Erlin Yustin Tatontos; Mohd Nazil Salleh (JURNAL INFO KESEHATAN, 2025)
The calculation of leukocyte types can be used to assess the level of infection or inflammation, particularly through the neutrophil-lymphocyte ratio (NLR). The NLR has been established as a useful biomarker for predicting bacteremia. Although differential leukocyte count and the neutrophil–lymphocyte ratio (NLR) have been widely proposed as indicators of infection and inflammation, their clinical interpretation remains unclear across disease states, particularly in tuberculosis. Current evidence is limited regarding how leukocyte profiles and NLR change during standard anti tuberculosis treatment (ATT), especially in the early and intermediate phases of therapy. Furthermore, it is not well established whether changes in leukocyte subtypes reflect treatment response or disease recovery in tuberculosis patients. Therefore, there is a need to quantify changes in leukocytes and NLR during TB treatment and to determine their potential role as readily accessible biomarkers for monitoring therapy outcomes. The goal of this study was to determine the effect of treatment duration on the number of polymorphonuclear cells, mononuclear cells, and the neutrophil-lymphocyte ratio as indicators of recovery in TB patients. This study employed a cross-sectional design with an analytical observational approach, involving 26 TB patients undergoing treatment for 1 to 6 months. The results showed the following average cell counts (per microliter) over the treatment period: basophils at 0.04, eosinophils at 0.30, neutrophils at 4.10, lymphocytes at 2.36, monocytes at 1.84, and a neutrophil-lymphocyte ratio of 0.53. One-way ANOVA analysis revealed a positive correlation between basophils, neutrophils, lymphocytes, monocytes, and the neutrophil-lymphocyte ratio with TB recovery. In conclusion, treatment of TB patients during the fourth to sixth month, or in the advanced phase of treatment showed differences in the number of  polymorphonuclear cells, mononuclear cells and  the NLR ratio compared to intensive phase treatment in TB patients at the Karang Taliwang and akranegara Health Centers.